2008
DOI: 10.1007/s10531-008-9363-y
|View full text |Cite
|
Sign up to set email alerts
|

Non-native plantation forests as alternative habitat for native forest beetles in a heavily modified landscape

Abstract: The once extensive native forests of New Zealand's central North Island are heavily fragmented, and the scattered remnants are now surrounded by a matrix of exotic pastoral grasslands and Pinus radiata plantation forests. The importance of these exotic habitats for native biodiversity is poorly understood. This study examines the utilisation of exotic plantation forests by native beetles in a heavily modified landscape. The diversity of selected beetle taxa was compared at multiple distances across edge gradie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(55 citation statements)
references
References 55 publications
6
49
0
Order By: Relevance
“…Even several endemic species have persisted only in exotic forests, e.g., species of the genus Tarphius (Coleoptera, Zopheridae) that seem to be adapted only to low altitudes, have been collected and persist in forests dominated by Acacia, Cryptomeria and Eucalyptus trees on the islands of Terceira, S. Jorge and Flores (Borges, 1991;Amorim, 2005). This important refuge role of planted forests has been emphasized on several occasions (Berndt et al, 2008;Bhagwat et al, 2008;Brockerhoff et al, 2008;Pawson et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Even several endemic species have persisted only in exotic forests, e.g., species of the genus Tarphius (Coleoptera, Zopheridae) that seem to be adapted only to low altitudes, have been collected and persist in forests dominated by Acacia, Cryptomeria and Eucalyptus trees on the islands of Terceira, S. Jorge and Flores (Borges, 1991;Amorim, 2005). This important refuge role of planted forests has been emphasized on several occasions (Berndt et al, 2008;Bhagwat et al, 2008;Brockerhoff et al, 2008;Pawson et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Species not forming patches of this size but which occurred frequently were also recorded. Nomenclature follows Stace (2010) for vascular plants and Paton (1999) for liverworts.…”
Section: Data Collectionmentioning
confidence: 99%
“…However, in countries where the extent of naturally occurring forests is limited, plantation forests may provide habitat for forest associated species and enhance overall landscape biodiversity, (Stephens and Wagner 2007;Brockerhoff et al 2008;Pawson et al 2008;Sweeney et al 2010;Coote et al 2012). Several studies have also suggested that plantation forests have the potential to benefit native diversity even where the planted tree species are nonnative conifer species (Bremer and Farley 2010;O'Hanlon and Harrrington 2012;Humphrey 2005).…”
Section: Introductionmentioning
confidence: 99%
“…However, objectively evaluating the value of plantations for conservation purposes is not trivial and requires assessing their contribution to biodiversity at higher spatial scales (Brockerhoff et al 2008). Hence, one should consider (i) whether plantations reduce harvest pressure on natural forests, (ii) what kind of land use or vegetation they replace, (iii) what other potential alternative land uses there are to be compared with, (iv) whether local species had enough time to colonize and adapt to the new habitat and (v) are plantations managed for production purposes only or with conservation goals in mind (Brockerhoff et al 2008).…”
Section: Are Plantations Biological Deserts?mentioning
confidence: 99%
“…Furthermore, some plantations can have communities as diverse as natural or secondary forests of birds (e.g., Clout and Gaze 1984, Brockie 1992, Kwok and Corlett 2000, fungi or invertebrate species (e.g., Humphrey et al 1999Humphrey et al , 2000Humphrey et al , 2002Ohsawa 2004). Moreover, plantations can have, in the absence of management strategies aiming at eliminating naturally occurring woody understory species, a "catalytic" effect by facilitating the colonization of early and even late successional tree species and other floristic elements from the surrounding forest (Brockerhoff et al 2008).…”
Section: Are Plantations Biological Deserts?mentioning
confidence: 99%